"It's not just about grades": Teachers' alternative perceptions of students performing at a low level and of these students' academic success. (October 2022) - Tan, Yuen Sze Michelle; Caleon, Imelda S.
Abstract: This study explored secondary teachers' perceptions of students performing at a low level and of these students' academic success, and how these perceptions shape instructional practices. Employing strength- and deficit-based perspectives, and phenomenography, we constructed categories to capture a range of conceptions that displayed varying degrees of student agency, with teacher empathy manifested at different levels. Ordering the categories based on phenomenographic methods enabled the identification of potentially 'powerful' ways the teachers responded to students' needs, which included engaging in partnerships to improve students' potential and moving away from examination-oriented definitions of success. Implications for research and practice are discussed.